2021
DOI: 10.1002/cbic.202100574
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring Enzyme Stringency Masks the Multispecificity of a Lyngbyatoxin (Indolactam Alkaloid) Nonribosomal Peptide Synthetase

Abstract: Indolactam alkaloids are activators of protein kinase C (PKC) and are of pharmacological interest for the treatment of pathologies involving PKC dysregulation. The marine cyanobacterial nonribosomal peptide synthetase (NRPS) pathway for lyngbyatoxin biosynthesis, which we previously expressed in E. coli, was studied for its amenability towards the biosynthesis of indolactam variants. Modification of culture conditions for our E. coli heterologous expression host and analysis of pathway products suggested the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Until now, little or no data about the contribution of L-serine dehydratase to microbial nematocidal activities has been reported. L-serine is an important biomolecule, and excessive amounts of intracellular serine inhibit the biosynthesis of other amino acids (Zhang et al, 2018(Zhang et al, , 2019Révora et al, 2020;Wang et al, 2020) essential to the production of certain bacterial toxins via the nonribosomal peptide synthetase (NRPS) pathway (Cao et al, 2008;Soeriyadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Until now, little or no data about the contribution of L-serine dehydratase to microbial nematocidal activities has been reported. L-serine is an important biomolecule, and excessive amounts of intracellular serine inhibit the biosynthesis of other amino acids (Zhang et al, 2018(Zhang et al, , 2019Révora et al, 2020;Wang et al, 2020) essential to the production of certain bacterial toxins via the nonribosomal peptide synthetase (NRPS) pathway (Cao et al, 2008;Soeriyadi et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…26,128 Additionally, in the pathway for the indole alkaloid lyngbiatoxin, an MbtH domain is observed fused to a cytochrome P450 in LtxB, an unusual arrangement that may promote protein-protein interactions of the P450 and a partner adenylation domain. 129,130 The MLP family is named aer MbtH, the rst described member that is in the mycobactin pathway of Mycobacterium tuberculosis. 131 Early studies demonstrated that deletion of MLP genes can completely or signicantly compromise the activity of an NRPS pathway.…”
Section: Bmdbcmentioning
confidence: 99%
“…For example, it was recently demonstrated that fluorinated building blocks can be incorporated into macrolide antibiotics by using engineered polyketide synthases [ 70 , 71 ]. Similarly, the lyngbyatoxin-producing nonribosomal peptide synthetase was engineered towards the production of pharmaceutically relevant indolactam variants [ 64 , 72 , 73 ].…”
Section: Pathway Optimization and Product Diversificationmentioning
confidence: 99%